A Roadmap to Digital Path: Empowering College Students in Cybersecurity - Anand Raj I.; R. Vidya (International Journal of Wireless Security and Networks, 2024)
A cybersecurity area that focuses on college students, digital citizens of our time, who play an important role in determining the future of cybersecurity. It focuses on the unique challenges college students face, from identity theft to cyber and sensitive data security. This report examines best practices and methods for building college students’ online barriers and underscores the need for digital literacy, literacy, and personal responsibility in an era of increasing and disappearing online risk. This shows the responsibility of universities to create a culture of cyber security among students. Looking forward, this article discusses possible approaches to online safety for college students. It covers a dynamic view of cyber threats, new technologies, and the need for adaptation and innovation. It describes the activities needed to educate the next generation of professionals with the knowledge and skills to navigate the cybersecurity environment, with a focus on education, awareness programs, and internships. In summary, this article explores the dynamic relationship between college students and cybersecurity, highlighting the challenges they face, best practices for protecting their digital worlds, and progress in this important sector.
Keywords: Cybersecurity; data protection; information security; online privacy; security policies